A glimpse into the DNA virome of the unique “living fossil” Welwitschia mirabilis - Debat, Humberto Julio; Bejerman, Nicolas Esteban (Elsevier, 2022)
Here, we report the identification and characterization of four novel DNA viruses from Welwitschia mirabilis transcriptomic and genomic datasets. Complete circular virus-like sequences with affinity to members of the Caulimoviridae and Geminiviridae families were detected and characterized from Welwitschia mirabilis genomic data. The two newly members of the Caulimoviridae family have been tentatively named as Welwitschia mirabilis virus 1 and 2 (WMV1-WMV2); whereas the two identified geminiviruses were named as Welwitschia mirabilis associated geminivirus A and B (WMaGVA-WMaGVB). Phylogenetic analysis suggests that WMV1-2 belong to a proposed genus of Caulimoviridae-infecting gymnosperms. WMaGVA-B are phylogenetically related with both mastreviruses and capulaviruses and likely represent a distinct evolutionary lineage within geminiviruses. Additionally, we detected several endogenous virus-like elements (EVE) linked to the discovered viruses in the recently reported W. mirabilis genome, suggesting a shared ancient evolutionary history of these viruses and the Welwithschia.